The Role of Exosomes in the Pathophysiology of Chronic Rhinosinusitis - Mueller, Sarina K. (Frontiers in Cellular and Infection Microbiology, 2022)
Non-invasive biomarker analysis has made repetitive and painless sampling over time possible. Exosomes are being released from a parent cell and their cargo mirrors the cell micromilieu of the parent cell. Therefore, exosomes are promising surrogates for their parent cells. That is also why exosomes provide an improved signal-to-noise ratio. Current studies have identified valid non-invasive biomarkers that may be able to monitor disease severity. Exosomes are suggested to play an important role in interepithelial communication and are suggested to play a role in the initiation and maintenance of inflammation in CRS. They are, however, also involved simultaneously in several immunological processes including immune protection and immunosuppression. As the isolation of exosomes is time-consuming their value in everyday routine diagnostics has yet to be determined.